Disclosure of Invention
In order to solve the problems of the technology, the application aims to disclose a preparation method of a hyperbranched succinate bio-based plasticizer and application thereof in plasticized PVC.
In order to achieve the aim of the application, the application adopts the following technical scheme:
in a first aspect, the application provides a preparation method of a hyperbranched succinate bio-based plasticizer, comprising the following steps:
(1) Carrying out melt polymerization reaction on glycerol and succinic acid under the action of a tin catalyst; the feeding ratio of the glycerol to the succinic acid is calculated according to the molar ratio of hydroxyl to carboxyl contained in the glycerol to the succinic acid: [ -OH ] [ -COOH ] =1.7-2.3;
(2) And (3) carrying out high-temperature vacuum treatment on the product obtained by melt polymerization to remove the micromolecule monomer and byproduct water, wherein the temperature of the high-temperature vacuum treatment is the same as the melt polymerization reaction temperature in the step (1), so as to obtain the hyperbranched succinate bio-based plasticizer, and storing the hyperbranched succinate bio-based plasticizer in a vacuum oven.
In the step (1) of the application, raw material monomers glycerin and succinic acid are used as bio-based raw materials, and when the molar ratio of hydroxyl groups to carboxyl groups is smaller than a certain value, the glycerin and succinic acid are subjected to crosslinking reaction, and the preferable ratio of the hydroxyl groups to the carboxyl groups is [ -OH ]: [ -COOH ] = 1.7-2.3, and the optimal ratio is [ -OH ]: [ -COOH ] = 1.7.
Preferably, the tin catalyst is dibutyl tin oxide, and the addition amount is 0.10-0.20 wt% of the total mass of glycerin and succinic acid, and most preferably 0.15wt%.
Preferably, in step (1), the melt polymerization temperature is 150 ℃ to 180 ℃, and more preferably the reaction temperature is 150 ℃; the reaction time is 8 to 20 hours, more preferably 20 hours.
Preferably, in the step (1), the high-temperature vacuum treatment condition is: the temperature is 150-180deg.C, more preferably 150deg.C, and the treatment time is 15-45 min, more preferably 30min.
Preferably, in step (2), the vacuum drying oven is kept at a temperature of 50℃to 70℃and more preferably at 60 ℃.
In a second aspect, the application provides the use of a hyperbranched succinate biobased plasticizer prepared according to the preparation method of the first aspect in plasticised PVC.
The application is specifically as follows: dissolving hyperbranched succinate bio-based plasticizer and polyvinyl chloride Powder (PVC) in a solvent, fully stirring and mixing, standing until the solution is clear and has no obvious bubbles, titrating the obtained solution on a glass plate to form a film by a solvent volatilization method, and finally removing the film to obtain the PVC film.
In the present application, PVC is selected from commercial products.
Preferably, the mass ratio of the hyperbranched succinate bio-based plasticizer to the PVC is 0.05-0.15, preferably 0.1.
Preferably, the solvent is tetrahydrofuran, ethanol, dimethylformamide, more preferably tetrahydrofuran.
Preferably, the solvent volatilization conditions are: drying in a blast oven at 45-80 ℃ for 1-3h, and optimally drying in a blast oven at 80 ℃ for 2h.
Compared with the prior art, the application has the beneficial effects that:
(1) The hyperbranched succinate bio-based plasticizer has the advantages of mature synthetic route, simple reaction device, simple and convenient operation, easily obtained raw materials, renewable raw materials, no toxicity and environmental protection, and reduced production cost;
(2) The hyperbranched succinate bio-based plasticizer is prepared by melt polymerization, does not need solvent conditions, omits steps such as intermediate product purification and the like, and can be used for industrial mass production.
(3) The hyperbranched succinic acid plasticizer synthesized by the application has excellent biocompatibility.
(4) The hyperbranched succinate bio-based plasticizer synthesized by the application has more excellent plasticizing effect when used for plasticizing PVC, and can greatly improve the mechanical property and migration resistance of PVC materials.
Detailed Description
In order to make the objects, technical solutions and advantages of the embodiments of the present application more clear, the technical solutions of the embodiments of the present application will be clearly and completely described below. The specific conditions are not noted in the examples and are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or apparatus used are not manufacturer-specific, are conventional products commercially available or can be prepared by known methods.
Example 1
2.5g of succinic acid and 2.2g of glycerin (the molar ratio of hydroxyl to carboxyl is 1.7) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 20 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was succinic acid honey-like consistency with a yield of 85.2% and a number average molecular weight of 3369Da.
The nuclear magnetic hydrogen spectrum of the product of example 1 is shown in figure 1, and the synthesized polymer structure can be proved to be hydroxyl terminated hyperbranched polyester by the nuclear magnetic hydrogen spectrum.
The hyperbranched succinic acid plasticizer synthesized in example 1 of the present application was subjected to a biocompatibility test according to GB/T16886.5-2017, and the experimental result is shown in FIG. 2, wherein the cell activity is 85% at a concentration of 0.2mg/ml, and meets the standard requirement (cell activity is more than 70%).
Example 2
2.5g of succinic acid and 2.2g of glycerin (the molar ratio of hydroxyl to carboxyl is 1.7) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 12 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was succinic acid honey-like consistency with a yield of 77.6% and a number average molecular weight of 2773Da.
Example 3
2.5g of succinic acid and 2.2g of glycerin (the molar ratio of hydroxyl to carboxyl is 1.7) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 8 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was a succinic acid honey-like consistency with a yield of 82.9% and a number average molecular weight of 2575Da.
Example 4
2.5g of succinic acid and 2.6g of glycerin (the molar ratio of hydroxyl to carboxyl is 2.0) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 20 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was succinic acid honey-like consistency with a yield of 79.3% and a number average molecular weight of 2415Da.
Example 5
2.5g of succinic acid and 2.4g of glycerin (the molar ratio of hydroxyl to carboxyl is 2.3) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 20 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was a succinic acid honey-like consistency with a yield of 78.6% and a number average molecular weight of 2199Da.
Example 6
2.5g of succinic acid and 2.2g of glycerin (the molar ratio of hydroxyl to carboxyl is 1.7) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 180 ℃ and the reaction time is 20 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was succinic acid honey-like consistency with a yield of 80.7% and a number average molecular weight of 2983Da.
Comparative example 1
2.5g of succinic acid and 2.23g of ethylene glycol are added into a reactor, the catalyst is used for 0.15 weight percent of the total mass of monomers, the reaction is carried out in an anhydrous oxygen-free nitrogen protection environment, the reaction temperature is 150 ℃, the reaction time is 12 hours, after the temperature of the reactor is reduced, 50ml of solvent dimethylformamide is used for dissolving the polymer, the polymer is poured into a beaker and added with magneton, 0.5g of sodium hydroxide and 0.5g of active carbon are added, stirring is carried out for 2 hours, the mixture is filtered by using 50 mu m filter paper, a 20ml glass bottle is used for collecting filtrate, the glass bottle containing the filtrate is moved into a vacuum oven at 80 ℃, and the solvent in the filtrate is removed by drying for 24 hours, so that light yellow waxy linear succinate is obtained, and then the light yellow waxy linear succinate is stored in the vacuum oven at 60 ℃, the yield is 77.6%, and the number average molecular weight is 1936Da.
Comparative example 2
2.5g of succinic acid and 1.69g of glycerin (the molar ratio of hydroxyl to carboxyl is 1.3) are added into a reactor, the dosage of the catalyst, namely, the dibutyltin oxide is 0.15 percent of the total mass of the monomers, the catalyst and the glycerin react in an anhydrous anaerobic nitrogen protection environment, the reaction temperature is 150 ℃ and the reaction time is 20 hours, then vacuum treatment is carried out for 0.5 hour at the same high temperature of 150 ℃ to remove micromolecule monomers and byproduct water, and hyperbranched succinic acid polyester is obtained and stored in a vacuum oven at 60 ℃. The product was a gummy viscous product with a yield of 66.2% and a number average molecular weight of 2530Da.
Comparative example 3
Commercial dioctyl phthalate (national pharmaceutical systems chemical Co., ltd.).
Example 7
PVC was plasticized using the materials obtained in example 1 and comparative examples 1 and 2 as plasticizers to obtain plastic test pieces. The preparation method comprises the following steps: 0.3g of plasticizer, 3g of PVC and 50ml of tetrahydrofuran are dissolved in a beaker container, stirred well and kept stand for 20min. And (3) dripping the mixture in the container on a glass plate with the size of 50cm by using a titration film forming method, drying the glass plate in a blast oven at 80 ℃ for 2 hours, and uncovering the film after the glass plate is cooled in air to obtain the PVC film. For comparison, pure PVC films without plasticizers were prepared. The resulting films were used for performance testing.
Performing plasticization performance evaluation, mechanical property and migration performance test on the obtained PVC film:
(1) Plasticizing Performance evaluation
The plasticizer-plasticized PVC films of example 1 and comparative example 1, as well as the pure PVC film, were tested using a differential scanning calorimeter to determine the glass transition temperature of the film to evaluate the plasticizer effect of the plasticizer, and as shown in table 1, it can be seen from table 1 that the glass transition temperature of the plasticizer-plasticized PVC product of example 1 was significantly reduced (the lower the glass transition temperature, the better the plasticizing effect thereof) compared to the plasticizer-plasticized PVC film of comparative example 1, the pure PVC film, because the molecular structure of the hyperbranched plasticizer was relatively complex, and generally contained a plurality of branched structures, which could introduce a certain degree of randomness and activity into the PVC molecular chain, thereby reducing the interaction force of the PVC molecular chain, increasing the reactivity of the molecular chain, and making the PVC molecule more susceptible to glass transition. Meanwhile, the hyperbranched plasticizer can form stronger interaction force with PVC molecules, but has smaller influence on the main chain mobility of PVC molecular chains. This means that the hyperbranched plasticizer does not hinder the movement of the main chain of the PVC chain, thus lowering the glass transition temperature of the PVC chain. The interaction force of the linear plasticizer is relatively weak, and the main chain mobility of the PVC chain is greatly influenced, so that the glass transition temperature of the PVC chain is relatively high.
Table 1: DSC test results table
(2) Evaluation of mechanical Properties
The plasticizer-plasticized PVC films of example 1, comparative example 2 were cut to obtain stretched film sample specimens, and tensile test was performed according to the relevant standards to evaluate the mechanical properties thereof. The results are shown in Table 2, and it can be seen from Table 2 that the PVC articles plasticized by the plasticizers of example 1 have higher mechanical strength than the PVC articles plasticized by the plasticizers of comparative examples 1 and 2, which indicates that the hyperbranched succinic plasticizer provides better plasticizing effect to PVC and also increases the tensile strength thereof. The high molecular weight polymer or resin in the hyperbranched plasticizer has crosslinking capability, and can form stronger connection between PVC molecular chains through crosslinking with the PVC molecular chains, so that the mechanical strength of the PVC product is improved. Meanwhile, the high molecular weight polymer or resin in the hyperbranched plasticizer has higher ductility, and can play a certain role in tensile resistance and tear resistance when the PVC product is subjected to external force, thereby improving the mechanical strength of the PVC product. Therefore, the hyperbranched plasticizer not only provides a better plasticizing effect for PVC products, but also remarkably improves the tensile strength of the material. This gives the hyperbranched structure plasticizer a significant advantage in the application of PVC articles.
Table 2: tensile test results table
(3) Migration performance assessment
The migration performance of the PVC films plasticized by the plasticizers of example 1, comparative example 1 and comparative example 2 was studied according to ASTMD1239-14, and the specific steps were: immersing a PVC test piece in deionized water, standing at 50 ℃ for 24 hours, taking out, washing with ethanol, drying in an oven at 40 ℃ for 2 hours, transferring into a dryer, cooling to room temperature, weighing, and calculating the mass loss of the PVC test piece before and after the experiment (only PVC and plasticizer are contained in the mixture, so that the reduction amount can be regarded as the migration amount of the plasticizer). As a result, as shown in table 3, it can be seen from table 3 that the plasticizer-plasticized PCV film of example 1 had a migration amount that was one time or more lower than that of the plasticizer-plasticized PVC films of comparative examples 1 and 2, sufficiently embodying the advantage of the hyperbranched structure, and was superior in migration resistance. This is because hyperbranched plasticizers have a higher molecular weight, which means that they have a lower solubility in PVC materials and a poorer compatibility with PVC. This poor compatibility makes it more difficult for hyperbranched plasticizers to migrate out of the PVC material. While hyperbranched structural plasticizers generally have the ability to form chemical bonds with PVC. This formation of chemical bonds can allow the plasticizer to be more firmly fixed in the PVC material, reducing the possibility of its migration. Spatial blocking effect: the molecular structure of hyperbranched plasticizers is relatively complex, often with branches or other special structures, which can form a certain spatial barrier effect between molecules. The space blocking effect can effectively limit the migration of the plasticizer and improve the migration resistance of the PVC product.
Table 3: migration test result table
Firstly, the hyperbranched plasticizer synthesized by the embodiment of the application has the characteristics of complex molecular structure, good solubility and diffusivity, good thermal stability and the like, so that the plasticizer is better than the linear plasticizer in the aspect of plasticizing performance of PVC products. Secondly, the characteristics of the more complex molecular structure, smaller influence on the mobility of the main chain, better plasticizing effect and the like of the hyperbranched structure plasticizer enable the plasticizer to reduce the interaction force of the PVC chain, improve the activity of the PVC molecular chain and further reduce the glass transition temperature of the PVC product. Finally, compared with linear plasticizers, the hyperbranched plasticizer has higher molecular weight, chemical bond forming capability and space blocking effect, and the characteristics enable the anti-migration performance of the hyperbranched plasticizer in PVC products to be better.
In summary, the application provides a method for producing hyperbranched succinic acid plasticizer, which is synthesized without solvent, can avoid complicated post-treatment steps, is easier to realize industrialization on the basis of renewable raw material sources, and has good biocompatibility through standard tests, so that the plasticizer is widely and safely applied and has good plasticizing effect. The hyperbranched succinic acid plasticizer synthesized by the application can greatly improve the mechanical property and migration resistance of the PVC material. Therefore, the hyperbranched succinic acid plasticizer has wide application prospect and has positive influence on the environment and the human health.
The above description is only an example of the present application and is not intended to limit the scope of the present application, and various modifications and variations will be apparent to those skilled in the art. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the protection scope of the present application.